Применение комбинированной программы регулирования для турбоустановок большой мощности с сопловым парораспределением - Бабаев, А. И.; Голощапов, Владимир Николаевич (НТУ "ХПИ", 2015)
В данной статье рассматривается вопрос изменения нагрузки действующих энергоблоков тепловых электростанций, имеющих турбины с сопловым парораспределением, путем применения комбинированной программы регулирования и определение эффективности использования режима скользящего давления в зависимости от различного количества открытых регулирующих клапанов и начальных параметров пара.

This paper gives consideration to the problem of a change of the load of the working energy blocks of thermal power stations that have turbines with steam distribution nozzles, using the combined control program and defining the efficiency of the use of sliding pressure mode depending on a different number of open control valves and initial steam parameters. The analysis of the test data and computational data showed that it is more preferable to use the combined control program switching over the energy block into the sliding pressure mode and fully opening the three valves for the turbines with supercritical parameters whose steam distribution structure has four control valves and each valve services its nozzle group; for operating turbines K-200-130 and K-160-130 that have two completely open valves the combined control program is considered to be more efficient; one of the promising ways of an increase in the efficient operation of the turbine plant with the combined control program can be the modernization of the control stage with the realization of its maximum efficiency in the mode close to nominal.
Aplication of the combined program to control turbine plants of a high power with the jet regulation
Keywords: тепловые электростанции; скользящее давление; парораспределение; регулирование энергоблока; переменный режим; combined control; sliding pressure; steam distribution; energy block control; variable mode